Cartografia, mapas e experimentações com linguagens da arte: processos de produção de outras geografias em educação - Pereira, Ernandes de Oliveira (2019)
This study was developed at the Federal Institute of Education, Science and Technology of Espírito Santo, in the environment of the Geographic Cartography and Socio-spatial Management Laboratory. It started with the following problems: how to enable the immanence of other geographies of space and place beyond textbooks, cliché images that restrict the students' thinking? As the language of art, can it mobilize other ways of thinking about space and place in the educational context? Faced with these questions, the following hypothesis was raised: the languages of art, such as photography and poetry, mobilize students' thinking about space and place, transcending textbooks, official images of places, allowing the immanence of other possibilities of geographies, from an invention perspective. In order to ratify this premise, the adopted methodology was anchored in cartography, as a process of monitoring the production of maps (other geographies) during and after experiments with the languages of the arts. Therefore, emotional reactions, discourses, drawings and artistic creations of the students themselves, in the field of photography and poetry, served as important elements for analysis in the light of the philosophy of difference of Gilles Deleuze and Felix Guattari. It was a singular journey of a teacher marked by many movements of paradigms. In that, the notions of space and place of textbooks, terrestrial globes, school atlas, seen as mere surfaces that support events, have been overcome. A brief journey, that took place in the Espírito Santo region, where the homogeneous image of the suffering and overcoming of the European immigrant overlies and erases other possibilities of trajectories, such as that of the indigenous and Afro-descendants whose ancestors were enslaved in former Portuguese farms. A journey marked by the posture of the foreigner as cartographer that accompanies the creative and subjective processes of the students when mobilized by the violent forces of the signs of the languages of art as poetry and photography. A journey that seeks to open connections, ruptures and possibilities so that other geographies can emerge within the educational environment.